Akibat Hukum Benda Objek Jaminan Fidusia yang diajukan Jaminan Ulang Hak Jaminan atas Resi Gudang - Soegih Rasyad Sriwidyandiyo; Felia Ramadhanty Waluyo; Nataya Shafa Ghaziya (UNES Law Review, 2023)
The purpose of this legal article is to identify whether the act of re-securing a Fiduciary Security Object through the granting of a Security Right over a Warehouse Receipt has a valid legal basis and the legal implications that arise. The approach adopted in this article involves analyzing the statutory aspects as well as the conceptual approach. The results of this study reveal that there are potential similarities in the category of collateral objects between fiduciary guarantees and warehouse receipt security rights. This situation has the potential to create problems. The regulation regarding the object of fiduciary guarantee is regulated in Law No. 42/1999 on Fiduciary Guarantee, while the object of guarantee relating to the Security Right on Warehouse Receipt is regulated in Law No. 9/2006 on Warehouse Receipt System, as amended through Law No. 9/2011 on Warehouse Receipt System. It is known that the act of applying for re-collateralization of the object of fiduciary guarantee through the granting of security rights over warehouse receipts does not have a strong legal basis and has the potential to cause legal consequences for the existence of the agreement and the position of creditors in the agreement.